Oral Floor and Gingival Metastasis of Cholangiocarcinoma: A Case Report and Review of the Literature - Yukihiro Nakanishi; Bo Xu; Charles LeVea (Hindawi Limited, 2014)
The oral cavity is very unusual site of metastases even though wide spread metastatic disease may be present. The most common primary sites that metastasize to the oral cavity are lung, kidney, breast, and hepatocellular carcinoma. We present a rare case of a 77-year-old Caucasian female with metastasis from a cholangiocarcinoma to the oral floor contiguous with lingual gingival mucosa. The patient presented with left sided rib pain. A CT scan of the chest, abdomen, and pelvis showed multiple pulmonary nodules and a single dominant mass in the right lobe of the liver. This tumor was 6.5 cm with multiple satellite lesions surrounding it. The liver biopsy was diagnostic of a moderately to poorly differentiated adenocarcinoma, consistent with a primary cholangiocarcinoma. After undergoing one cycle of gemcitabine chemotherapy, the patient noticed an extremely rapidly growing mass involving her right lower gingiva and the entire right floor of her mouth. The biopsy of that mass also showed a moderately to poorly differentiated adenocarcinoma. The gingival tumor had a similar cytomorphology and immunophenotype as her cholangiocarcinoma. Therefore, an unusual site for metastatic cholangiocarcinoma was confirmed.